Chemical Castration of Rabbits Via Intratesticular Injection of Ethanol or Formalin - Majeed, A. A . (The Iraqi Journal of Veterinary Medicine, 2011)
The purpose of the study was to determine the efficacy and safety ofintratesticular injection of ethanol or formalin as a novel method forchemosterilization of rabbits. Twenty rabbits, aged (6-8 months) and weighed(1.3-1.5) kg were used. They were randomly divided into two equal groups. Inthe first group, absolute ethanol and in the second group, formalin1% at a doseof 1ml/testis for each agent were injected under the effect of xylazine, byinsertion of the needle from the caudo-ventral aspect of the testis then pushed inthe center of the testis toward the cranio-dorsal pole of the testis. Orchidectomywas done at first and second months postinjection, samples from the testes andepididymis were taken for histopathological evaluation of testicular changes.Histopathological examination revealed atrophy of the seminiferous tubules,degeneration or vacuolation of sertoli cells and the leydig cells replaced byfibrous connective tissue. The of epididymis show narrowing of the epididymallumen. The severity and distribution of the lesions were more pronounced informalin group, although both agents had the ability to induce sterilization inrabbits.